In vitro culture of mouse embryos in human amniotic fluid - Coetzee, J C; Sevenster, C B; Fourie, F L; van der Merwe, J V; Helberg, L A (South African medical journal, 1989)
Human amniotic fluid was compared with Ham's F-10 culture medium as a possible alternative for use in in vitro fertilisation. The cleavage success of mouse embryos in human amniotic fluid (experimental group) was 92% compared with 86% in Ham's F-10 medium. It is concluded that human amniotic fluid is a viable alternative culture medium for mouse embryos.